EAACI Position paper on the standardization of nasal allergen challenges. Issue 8 (27th March 2018) - Augé, J.; Vent, J.; Agache, I.; Airaksinen, L.; Campo Mozo, P.; Chaker, A.; Cingi, C.; Durham, S.; Fokkens, W.; Gevaert, P.; Giotakis, A.; Hellings, P.; et al.
Abstract: Nasal allergen challenge (NAC) is an important tool to diagnose allergic rhinitis. In daily clinical routine, experimentally, or when measuring therapeutic success clinically, nasal allergen challenge is fundamental. It is further one of the key diagnostic tools when initiating specific allergen immunotherapy. So far, national recommendations offered guidance on its execution; however, international divergence left many questions unanswered. These differences in the literature caused EAACI to initiate a task force to answer unmet needs and find a consensus in executing nasal allergen challenge. On the basis of a systematic review containing nasal allergen challenges of the past years, task force members reviewed evidence, discussed open issues, and studied variations of several subjective and objective assessment parameters to propose a standardized way of a nasal allergen challenge procedure in clinical practice. Besides an update on indications, contraindications, and preparations for the test procedure, main recommendations are a bilaterally challenge with standardized allergens, with a spray device offering 0.1 mL per nostril. A systematic catalogue for positivity criteria is given for the variety of established subjective and objective assessment methods as well as a schedule for the challenge procedure. The task force recommends a unified protocol for NAC for daily clinical practice, aiming at eliminating the previous difficulty of comparing NAC results due to unmet needs.